The implementation of teaching model to induce simson tarigan's concept change (m3pk) to improve student chemistry learning outcomes in the subject of reaction equation class x man binjai - Dwy Puspita Sari; Marini Damanik; Simson Tarigan (Pascasarjana Universitas Negeri Medan, 2018)
This study aims to determine the improvement of students' chemistry learning outcomes by applying M3PK. The population were all students of class X MIA. The sample consisted of two classes, namely class X MIA 2 and X MIA 3 which were taken by random sampling. The first class is used as an experimental class which is taught using the Teaching Model to Induce Change of Concepts, and the second class as a control class which was learnt by using the Direct Instruction. As a prerequisite for testing the hypothesis, the study data of the two sample groups were tested for normality and homogeneity and the data achieved from both sample groups were normal and homogeneous. In testing, the hypothesis obtained the price of tcount> ttable (4.619> 1.670). It shows that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, which means that the increase in learning outcomes of chemistry students who are learnt by using M3PK is higher than the learning outcomes of chemistry students who are educated using the Direct Instruction. The percentage increased in students' learning outcomes of chemistry learnt by using M3PK was 74.5% while those taught using the Model Direct Instructionwere 64.8%.Keywords:equation reactions; m3pk; learning outcomes